METHODOLOGY OF TEACHING DESCRIPTIVE GEOMETRY USING DIGITAL EDUCATIONAL RESOURCES: ENHANCING LEARNING AND ENGAGEMENT (American Journal of Pedagogical and Educational Research, 2025)
The advancement of digital educational resources has revolutionized teaching methodologies, particularly in fields requiring spatial reasoning and geometric understanding, such as Descriptive Geometry. Digital resources—including interactive simulations, virtual laboratories, 3D modeling software, and online assessment tools—enable educators to deliver more engaging, flexible, and effective instruction. This study explores methodologies for teaching Descriptive Geometry through digital educational resources, focusing on pedagogical strategies, platform design, and learner engagement. Using the IMRaD framework, the research combines literature review, case studies of digital classroom implementation, and evaluation of student performance and engagement metrics. Results indicate that incorporating digital resources significantly enhances comprehension, visualization skills, and motivation, while facilitating individualized learning and immediate feedback. The discussion addresses pedagogical design principles, technological integration challenges, and recommendations for best practices in digitally-mediated Descriptive Geometry instruction. The conclusion emphasizes the critical role of digital educational resources in modernizing geometry education and improving learning outcomes.